Pendekatan Sejarah dalam Kajian Tafsir: Relevansi Kontekstual terhadap Pemahaman al-Qur’an di Era Modern - Moh Saepudin, Dindin; Rusydati Khaerani , IzzahFaizah Siti; Burhanuddin , Bunbun Muhammad (Jurnal Al-Mubarak: Jurnal Kajian Al-Qur'an dan Tafsir, 2025)
The historical approach to tafsir reflects the transformation of understanding of the Qur'an, which is not limited to doctrinal aspects, but also encompasses the complex social phenomenon. This approach allows researchers to analyze the Qur'an in a broader context, connecting the sacred text with the social, cultural, and political conditions of its time. This approach provides a broader perspective on the meaning of the Qur'an. The method used in this study is qualitative with a literature review approach, which examines how the historical approach has developed from the era of the classical scholars to the present. The results of the study show that understanding the Qur'an through a historical approach provides new insights relevant to contemporary contexts. By analyzing lafaz (words), the background of the verses, and socio-linguistic aspects, this study aims to understand the meaning of the verses of the Qur'an more deeply. This approach not only enriches tafsir studies, but also contributes to a more comprehensive and contextualized understanding of Islam, making it relevant in addressing the challenges of the modern era.